Patient-Generated Data as Indicators of Impact of Multidisciplinary and Multi-stakeholder Health Care Systems, in the Age of Personalised Medicine - Paola Zaratin; Per Soelberg Sørensen; Óscar Fernández; Giancarlo Comi (Neurology and Therapy)
Abstract Using the case study of the Multiple Sclerosis Care Unit Initiative launched by the European Charcot Foundation, we discuss the need to evaluate the impact of multidisciplinary and multi-stakeholder healthcare systems on patient-reported experience and outcomes for the programming and monitoring of brain and neurodegenerative diseases in Europe and beyond. The multiple sclerosis (MS) case study presented in this paper highlights the role of patient-generated data as indicators of the impact of value-based healthcare (VBHC) for all the different neurological diseases whose prodromal symptoms are the first signs of disease progression and therefore instrumental markers for preventive treatments to preserve brain health. A holistic approach to the treatment of MS plays a crucial role in the inclusion and scientific meaning of the patient’s perspective in terms of patient-reported dimension and patient-generated health data (PGHD).